Transparent Ceramics Fabricated via Spark Plasma Sintering–Magnesium Aluminate Spinel with Increased Aspect Ratio; Reviews and Advances in Chemistry; Vol. 14, iss. 3 - Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Deulina D. E. Darjya Evgenjevna; Stepanov S. A. Sergey Aleksandrovich; Shevchenko I. N. Ivan Nikolaevich; Huang Fuli; Valiev D. T. Damir Talgatovich; Tolkachev O. S. Oleg Sergeevich; Ilela A. E. Alfa Edison; Paygin V. D. Vladimir Denisovich (2024, 2024)
Title screen